Antimicrobial Activity of Friedelan-3β-ol and trans-N-Caffeoyltyramine Isolated from the Root of Vitis trifolia - PATNAIK, TANUSHREE; DEY, R.K.; GOUDA, PANCHANAN (Asian Journal of Chemistry, 2010)
This paper reports friedelan-3β-ol (1) and trans-Ncaffeoyltyramine (2), two possible organic substrates, isolated from the root of Vitis trifolia. The antimicrobial activity of isolated compound 1 was explained on the basis of presence of hydroxyl groups in the structure capable of forming hydrogen bonds with the active sites of the target enzymes. The presence of aromatic rings and phenolic hydroxyl group could be the contributing factors for the observed higher antimicrobial activity of compound 2.